Generation and purification of CD8+ melan-A-specific cytotoxic T lymphocytes for adoptive transfer in tumor immunotherapy. - Oelke, M; Moehrle, U; Chen, J; Behringer, D; Cerundolo, V; Lindemann, A; Mackensen, A (2000)
Tumor antigens that might serve as potential targets for adoptive T-cell therapy have been defined in different tumor entities, especially in malignant melanoma. To generate conditions to induce primary T-cell responses against different HLA-A*0201-restricted melanoma peptides and to allow further expansion of peptide-specific T cells for adoptive transfer, CD8+-purified T cells from healthy donors were stimulated with Melan-A-pulsed autologous dendritic cells. Dendritic cells were generated in vitro from monocytes with granulocyte macrophage colony-stimulating factor, interleukin-4, and transforming growth factor-beta1. After 3-4 weekly stimulation cycles with Melan-A-pulsed DCs, we were able to induce a strong peptide-specific CTL response in vitro. MHC-peptide tetramer staining revealed a frequency of up to 3.5% CD8+/Melan-A+ T cells. Additional antigen-independent expansion with anti-CD3/anti-CD28 monoclonal antibodies together with interleukin-2 gave rise to 600-fold expansion of CD8+ CTLs that maintained Melan-A specificity and were able to efficiently lyse Melan-A-expressing melanoma cells. To enrich antigen-specific T cells in vitro, we used a recently established technology for analysis and sorting of live cells according to secreted cytokines. In the present study, we demonstrated that Melan-A-specific T cells can be purified by magnetic separation according to secreted IFN-gamma. These cells revealed a very potent monospecific CTL response, even at low E:T ratios, against Melan-A-pulsed and Melan-A-expressing target cells. Altogether, our study demonstrated that we have developed an efficient method for generating large numbers of peptide-specific T cells in vitro that may be used for adoptive T-cell transfer in tumor immunotherapy.